Partisipasi Politik Masyarakat Kecamatan Medan Maimun Pada Pemilihan Gubernur Sumatera Utara Tahun 2018 - Faiz Albar Nasution; Kushandajani Kushandajani (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2019)
Community participation in the use of voting rights becomes the most important indicator of the success of regional elections. However, the recapitulation result of PILGUBSU year 2018 shows the participation rate of the city of Medan as big 55.80%, so not achieved target of KPU Medan City for 78% and community participation of Medan Maimun subdistrict only 48.12% which makes the participation lowest of the 21 subdistricts in the city of Medan. This research aims to analyze the political participation of the city of Medan in PILGUBSU in 2018 (case study: community of subdistricts Medan Maimun. The research method used is a qualitative descriptive. Analysis of data used refers to the opinion of Milles and Huberman among others: data reduction, display data and draw conclusions. The results showed first, the hierarchy of political participation of the subdistricts community. Medan Maimun is dominated by participation in the giving of votes and apathy total. Secondly, the factors influencing community participation in PILGUBSU year 2018 are: Political consciousness, belief in government, social status and economic status, political affiliation of parents and organizational experience.